Risk factors of incident in-hospital pulmonary embolism and its outcomes: autopsy study data - O. Ya. Vasiltseva; I. N. Vorozhtsova; A. V. Krestinin; E. V. Stefanova; R. S. Karpov (Кардиоваскулярная терапия и профилактика, 2012)
Aim. Based on the autopsy data, to investigate the role of various risk factors (RFs) in the development of the incident cases of pulmonary thromboembolism (PTE) and their outcomes among the patients who died in Tomsk City hospitals (2003-2010). Material and methods. The analysed data came from autopsy protocols and medical histories of all patients (n=651) who had PTE diagnosed prior to or after death and who died in Tomsk hospitals between March 1st 2003 and December 31st 2010. The pathologoanatomical examination used the total evisceration technique by Shor. Data analysis was performed with the Pentium-V software package “Statistica for Windows”. The impact of RFs and treatment on the PTE outcome was assessed in a statistical model. Results. The presence of two or three RFs was associated with a higher risk of fatal in-hospital PTE. Overall, the risk of fatal PTE was explained by RF patterns (56,0%), inadequate treatment (43,9%), and other factors (0,1%). Conclusion. The identified features of the impact of RFs and medical treatment on the PTE outcome in Tomsk hospitals (2003-2010) should be taken into consideration when planning the strategy of improving the effectiveness of diagnostics, prevention, and treatment programmes.